Negotiating gender in the male-dominated skilled trades: a systematic literature review. Issue 10 (2nd October 2020) - Bridges, Donna; Wulff, Elizabeth; Bamberry, Larissa; Krivokapic-Skoko, Branka; Jenkins, Stacey
Abstract: Occupations in the skilled trades are highly segregated with women comprising 1–3% of this workforce in Western nations. We report on a systematic review of 26 articles, from 1998 to 2019, which explored women's recruitment and retention in the skilled trades. Two research questions underpinned the review; the first identified challenges and barriers, the second identified success factors. Furthermore, the review examines why percentages of tradeswomen remain lower than those of women in professional occupations within the industry. The literature included in this review focuses on the barriers to women's employment without sufficient emphasis on solutions to overcoming those barriers. The most common explanation for the problems of recruitment and attrition made in the literature is the failure of the masculine culture to change. However, we found little theoretical examination of masculinity and masculine culture beyond the hegemonic binary. Whilst many of the barriers exist for all women in construction, we argue that two distinct factors impact women in the skilled trades more than women in other occupations in the industry. These are the gendered body and informal and unregulated employment practices. These significant points of difference shed light on the future focus for research about women in the skilled trades.